Test performance study of diagnostic procedures for identification and detection of Gibberella circinata in pine seeds in the framework of a EUPHRESCO project. (16th July 2013) - Ioos, R.; Annesi, T.; Fourrier, C.; Saurat, C.; Chandelier, A.; Inghelbrecht, S.; Diogo, E. L. F.; Pérez‐Sierra, A.‐M.; Barnes, A. V.; Paruma, K.; Adam, M.; van, P.; et al.
<x xml:space="preserve">Abstract</x> Gibberella circinata (anamorph Fusarium circinatum) is a harmful fungus infecting pine trees that has been subject to European Union emergency phytosanitary measures since 2007. This fungus is spread over long distances primarily via pine seeds, consequently reliable detection tools and methods are needed to test pine seed lots imported and marketed in the EU. Several detection methods are available in the scientific literature but very limited validation data is available. For that purpose, one European EUPHRESCO project called 'Gibcir‐Diagseed' was launched, involving 10 countries. This project aimed to select and validate one or more diagnostic procedures targeting this pest via inter‐laboratory tests, as well as a suitable sampling method. Performance criteria were calculated for three procedures chosen by participants: isolation followed by morphological characterization, isolation followed by conventional PCR and biological enrichment followed by real‐time PCR. The results showed that all three procedures provided acceptable performance criteria but also demonstrated that none of them could generate 100% of correct results. Regarding the sampling issue, the National Plant Protection Organizations consultation enabled an agreement to be reached on the number of seeds to be tested: 400 per sample, for a 95% confidence level that an infection of at least 1% will be detected.